A Big Fish in a Small Pond: Ability Rank and Human Capital Investment - Elsner, Benjamin; Isphording, Ingo E. (Journal of Labor Economics, 2017)
We study the impact of a student’s ordinal rank in a high school cohort on educational attainment several years later. To identify a causal effect, we compare multiple cohorts within the same school, exploiting idiosyncratic variation in cohort composition. We find that a student’s ordinal rank significantly affects educational outcomes later in life. Students with a higher rank are significantly more likely to finish high school and to attend college. Exploring potential channels, we find that students with a higher rank have higher expectations about their future career, as well as a higher perceived intelligence.